개인정보 영향평가 수행 사례에 기반한 기관의 개인정보보호법 대응방안에 관한 연구 - 조성규; 전문석; Cho, Sung Kyu; Jun, Moon Seog ((사)디지털산업정보학회 논문지, 8(1), 2012)
According to the enforcement of Personal Information Protection Act as of September 2011, the laws and regulations for the protection of personal information that were applied only to the certain sectors such as information & communication network, financial institutions, public sector etc. for the time being has been expanded to apply to all public and private sectors to process personal information. In particular, because the public institutions are obliged to be mandatorily conducted of the Privacy Impact Assessment, it will be enforced in earnest for each agency's informationization business that handles personal information. In this paper, I examine the most derived vulnerability and set up the improvement measure to supplement it with the examples of 10 of all the institutions conducting the Privacy Impact Assessment in the year 2011. And, I suggest the measures to be prepared by the institutions to observe the Personal Information Protection Act.